PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS MELALUI KEPUASAN PELANGGAN BOLT - Susilowati Susilowati; Tati Handayani (Ekonomi dan Bisnis, 2015)
This study was conducted to examine the magnitude of the contribution proposed by the coefficient lines at each track diagram of causal relationships between variables of Product Quality and Price on Customer Loyalty Provider Bolt Through Customer Satisfaction. The population in this study is that user Provider Bolt in Pondok Pinang Rw 012 South Jakarta with a sample of 70 people. Sampling technique using a Non-probability Sampling Simple Random Sampling technique. The analysis technique used is the Path Analysis and the obtained results of the coefficient of direct influence Product Quality and Price on Customer Satisfaction at 0,776 while the coefficient of indirect influence on the Product Quality and Price of Customer Loyalty through Customer Satisfaction is 0,688. Therefore the direct influence coefficient greater than the coefficient of direct influence.